Análise dos casos de beribéri em indígenas e não indígenas notificados no Brasil, 2013-2018 - ASSUNÇÃO, Anne Karine Martins (2021)
Beriberi is a clinical manifestation of severe and prolonged thiamine (vitamin B1) deficiency, of a multi-causal nature, and usually associated with poverty and food insecurity among vulnerable populations such as indigenous people. The objective of the first article was to perform a spatial analysis of cases of beriberi in indigenous people notified in Brazil from 2013 to 2018. Cross-sectional study with time series data of suspected cases of beriberi reported to the Ministry of Health through FormSUS between July 2013 and September 2018. Indigenous villages were georeferenced and Kernel density estimation was used to identify spatial distribution patterns of beriberi cases. From 2013 to 2018, 414 cases of beriberi were reported in the country, of which 210 (50.7%) were indigenous. All cases in indigenous peoples occurred in states located in the Legal Amazon (Maranhão, Roraima and Tocantins). Kernel density estimation showed high density areas in Tocantins and Roraima. The aim of the second article was to compare cases of beriberi in indigenous people with cases in non-indigenous people in Brazil. This is a cross-sectional study of notified cases of beriberi from 2013 to 2018 through the Ministry of Health's FormSUS. The study variables were used: 1) sociodemographic variables; 2) clinical, behavioral and health service variables; 3) variables constructed for analysis: indigenous (yes, no); performs manual work. For statistical analysis, STATA® software version 14.0 was used. Indigenous and non-indigenous cases were compared using the chi-square test or Fisher's exact test with a significance level of p<0.05. Reported consumption of alcoholic beverages: 58.1% of indigenous people and 71.6% of non-indigenous people (p=0.004), additionally 71.0% of indigenous people consumed caxiri (traditional fermented alcoholic beverage). They reported making daily physical effort: 76.1% of the indigenous people and 40.2% of the non-indigenous people (p<0.001). Beriberi in the country affects more indigenous people and is related to alcohol consumption and physical exertion. The findings can be used to guide actions that contribute to the monitoring and prevention of beriberi among indigenous peoples.